PRESERVING CULTURAL HERITAGE THROUGH CUISINE: SYMBOLIC MEANINGS OF NASI HADAP-HADAPAN IN MALAY WEDDINGS IN TANJUNG BALAI - Lubis, Suci Ramadhani; Purwarno, Purwarno; Sahri, Zulfan; Suhendi, Andang (Universitas Islam Sumatera Utara, 2025)
Food plays a pivotal role in the construction of cultural identity and the preservation of intangible heritage across societies. This study explores the symbolic meanings embedded in the Nasi Hadap-Hadapan tradition, a central element in Malay wedding rituals in Tanjung Balai, North Sumatra. The practice of Nasi Hadap-Hadapan—a ceremonial meal shared by the bride, groom, and their families—represents not only a social gathering but also a transmission of philosophical values and cultural wisdom. Using a qualitative descriptive method, data were collected through interviews with cultural practitioners, community elders, and government officials, complemented by participant observation. The findings reveal that each component of the food—such as rice, ayam masak bulat (whole chicken), assorted cakes, sweets, and vegetables—carries symbolic meanings that reflect prosperity, harmony, perseverance, and readiness for married life. Despite its deep cultural significance, the tradition is increasingly perceived as a form of entertainment rather than a sacred practice, largely due to modernization and diminishing intergenerational knowledge. This article argues that revitalizing and contextualizing Nasi Hadap-Hadapan is essential for safeguarding Malay intangible heritage while reinforcing social cohesion in multicultural Indonesia.